Effectiveness of Workshop on Nurse Stigma for ODHA - Elli Yus Setyaningrum; Ernawati Ernawati; Sri Rejeki (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stigma against HIV/AIDS patients remains a significant challenge in healthcare services, including among nurses. This study aims to examine the effectiveness of workshop interventions in reducing nurses' stigma towards People Living with HIV/AIDS (ODHA) at Kesesi Regional Hospital, Pekalongan Regency. The method used is a systematic literature review with article searches in Google Scholar, PubMed, Proquest, and ScienceDirect databases within the 2019-2024 publication range. Inclusion criteria included journal articles on educational interventions in reducing HIV/AIDS stigma, both in Indonesian and English. From 122 identified articlesA total of 10 articles were selected that met the inclusion criteria. After getting several journals that match the theme, then do the elimination according to the similarity of the author's title, journals that have similar titles and inclusion criteria are then analyzed. The results showed that various intervention approaches proved effective in reducing HIV/AIDS stigma, including technology-based interventions, interactive workshops, and conventional health education. Interventions that combined participatory approaches, skills training, direct contact with affected groups, and structural changes showed optimal results in reducing stigma in healthcare facilities.